Association between glycated hemoglobin and functional outcomes in patients with intracranial large artery atherosclerotic disease-related acute ischemic stroke: identifying the magic number - Zafar, Azra; Albakr, Aishah; Shahid, Rizwana; Alkhamis, Fahd; Alabdali, Majed; Aljaafari, Danah; Nazish, Saima; AlShamrani, Foziah Jabbar Gossab; Shariff, Erum; Zeeshan, Mohammad; AlSulaiman, Abdulla; AlAmri, Abdullah Saleh; et al. (Frontiers in Neurology, 2023)
Objective: This study aimed to investigate the effect of glycated hemoglobin A1c (HbA1c) level on functional outcome (FOC) in patients with intracranial large artery atherosclerotic disease (ICLAD)related acute ischemic stroke (AIS). Methods: This retrospective study enrolled patients with ICLAD-related AIS who were admitted to King Fahd University Hospital between January 2017 and September 2021. Patients were divided into two groups based on the optimal cutoff HbA1c level determined using receiver operating characteristic curve analysis-those with HbA1c ≤6.9% and those with HbA1c ˃6.9%. Demographic and other clinical characteristics were compared between the two groups using chi-square tests. The association between HbA1c and 90-day FOC was assessed using the chi-square test and odds ratios (ORs). Multivariate analysis was performed to adjust for confounding factors. Results: A total of 140 patients were included in the analysis. A significant association was observed between HbA1c level and FOC. Compared to patients with HbA1c ≤6.9%, patients with HbA1c ˃6.9% were more likely to have an unfavorable FOC (p = <0.001, OR = 2.05, 95% confidence interval [CI] = 1. 33-3.14). The association between HbA1c ˃6.9% and unfavorable FOC was sustained even after adjusting for confounding factors (p = 0.008) and atherosclerosis risk factors (p = 0.01). HbA1c ˃6.9% was also associated with higher ORs for in-hospital complications This is a provisional file, not the final typeset article (p = 0.06, OR = 1.34, 95% CI = 1.02-1.77) and mortality (p = 0.07, OR = 1.42, 95% CI = 1.06-1.92), although these associations did not attain significant p values. Conclusion: HbA1c ˃6.9% was significantly associated with unfavorable FOC in ICLAD-related AIS. However, further studies with larger sample sizes are required to verify whether HbA1c is an independent predictor of poor FOC. Nevertheless, targeting HbA1c <7% should be the goal of physicians when managing patients at high risk of ICLAD.